The impact of the intervention of NGOs and CBOs on Lesotho’s governance - Koali, Seemola Sylvia (University of the Free State, 2023)
Lesotho is a small, mountainous landlocked country, it is land locked by South Africa. It has a population of almost 2.3 million and nominal gross domestic product (GDP) per capita of $1,045.9 in 2022 (World Bank 2023). Like other African countries in its pursuit to strengthen its democracy and reduce poverty, Lesotho became a member and signatory to several sub-regional, regional, and international convention. These organisations include the Southern African Development Communities (SADC), the Southern African Customs Union (SACU), the United Nations (UN), and the African Union (AU). As mechanisms to help in the fight against poverty and global development, many countries introduced Non-Governmental Organisations (NGOs) and Community Based Organisations (CBOs) to their governance (processes/structures?) to fill gaps that the government either cannot or do not wish to fulfill. Loise (2017) notes that NGOs are one of the basic elements of democratic societies. It is incontestable that NGOs and CBOs have come to play a prominent role on the African continent, including Lesotho. They are regarded as one of the mechanisms used in poverty reduction initiatives and programmes. The roots of NGOs and CBOs in Africa are found in the arrival of missionaries on the continent who dispensed charity and engaged in the provision of education and health services (Manji and O’Coill 2007: 568). Matthews and Nqaba (2017: 5) argued that while the history of NGOs could be traced back to the colonial period, it was in the 1980s that they were increasingly recognised as important institutions in the broader development aid sectors in Africa, as well as the rest of the world. Khati (2018: iii) observed that the prevalence of NGOs and CBOs in most developing countries is linked to the availability of foreign aid and a modernisation agenda for developed countries to invest in the development of the Global South countries. Khati (2018) states that, for these reasons, the governments of developing countries have embraced the existence and importance of NGOs in the improvement of the livelihoods of poor people within their regions.
Dissertation(M.A. (Governance and Political Transformation))--University of the Free State, 2023
Keywords: Lesotho government; Southern African Development Communities (SADC); Southern African Customs Union (SACU); United Nations (UN); African Union (AU); Non-Governmental Organisations (NGOs); Community Based Organisations (CBOs); Global South